Investigating the Effect of Temperature on the Efficacy of Agicoat© Silver Nanocrystal Dressing Through Its Impact on Staphylococcus aureus Under Varying Temperature Conditions - Fathabadi , Majid; Maddah, Soroush; Barghamadi , Hamideh (Management Strategies and Engineering Sciences, 2025)
In a case study, the results of two experiments conducted at 30 °C and 37 °C demonstrated that Agicoat© silver nanocrystal dressing exhibits enhanced performance in eliminating microbial agents at 37 °C. This observation gave rise to the hypothesis that regulating the environmental temperature may serve as a method to reduce the duration of treatment—an aspect that has been largely overlooked in current therapeutic approaches. According to the recommendations of the U.S. Centers for Disease Control and Prevention (CDC), the standard temperature advised for patient hospital rooms is 24 °C, and in general, physicians do not incorporate room temperature as a variable in treatment protocols. Therefore, in this study, through laboratory experiments, we investigated the effect of increased ambient temperature on Agicoat© silver nanocrystal dressings, a product developed in Iran. After preparing dressing samples containing microbes at three concentrations—low, high, and no microbial presence—they were incubated for durations of 8 and 24 hours at various temperatures ranging from 18 °C to 37 °C. The investigation was conducted in two parts: a chemical assessment measuring silver ion release, and a microbiological assessment measuring the bactericidal efficacy against Staphylococcus aureus. The findings of this study led to the formulation of a protocol for adjusting the room temperature in patient care settings. By doing so, the treatment duration can be reduced, which in turn shortens hospitalization time, increases healthcare efficiency, reduces the financial burden on health insurance systems, and helps address the national shortage of hospital beds.